Persepsi Pedagang Pasar Kota Langsa terhadap Riba: Resistensi atau Toleransi - Muhammad Dayyan; Rifyal Dahlawy Chalil (IAIN Langsa, 2018)
The merchants in the Langsa city believe that usury (riba) is forbidden, yet they do not mind doing transactions with conventional bank which operated its activity based on the interest system. This research aims to analyse and examine the level of knowledge possesed by the merchants in the traditional market in related to the concept of riba, the reasons (factors) affecting merchants to transact with the conventional bank, and their attitudes on the decision (fatwa) given by the Council of Islamic Scholars of Indonesia (DSN-MUI). This a survey based-research which uses a descriptive approach (merchants in the Langsa city) as the research subject. The result shows that the majority of the merchants have a profound understanding on the prohibition of interest (riba) and that the role of DSN-MUI as the obligated council in setting the fatwa whichneeds to be followed, however they do not mind interacting with the conventional banks. This findings imply that there is an active role of Islamic banking in providing information on credit financing, a special scheme financing products which provide market traders a credit facilities, as well as the role of local government in assisting, guiding and supervising the implementation of credit through its policies and rules. Therefore, it is expected that market traders will be more motivated in applying bank loans.